Development of gold nanoparticles stabilized by PLGA and PVA for application in photothermal therapy - Borges, Soraia; Fernandes, Natanael; Moreira, André F. (Frontiers in Cell and Developmental Biology, 2026)
IntroductionIn today's world, cancer remains a major public health problem. Consequently, there has been a focused investigation of alternative therapeutic approaches to address this ongoing health concern. In this study, PLGA-gold nanomaterials were produced through various processes to determine whether these variations affected their structural integrity and, consequently, their physicochemical properties.MethodsThe PLGA-gold nanomaterials were produced through an oil-in-water (O/W) process (Formulation A) or a water-in-oil-in-water (W1/O/W2) process (Formulation B). The nanomaterials' physiscochemical properties were characterized by electron microscopy, dynamic light scattering, and UV-vis. Photothermal studies were performed using a 808 nm NIR laser and the PLGA-gold nanomaterials cytocompatibility was evaluated using resazurin.ResultsBoth methods originated particles with similar size and charge, 276.8 and –19.6 mV for formulation A and 317.5 nm and –18.6 mV for formulation B. Nevertheless, the TEM images revealed structural differences, with formulation A presenting the gold spheres clustered in the particle nucleus, whereas in formulation B the gold spheres were found in the outer PLGA shell. Moreover, upon irradiation with a NIR laser (808 nm, 1.7 W cm–2, 10 min), the particles showed a concentration dependent photothermal effect, promoting a temperature increase of 21 °C and 13.9 °C for formulation A and B at 400 μg/mL, respectively. Additionally, preliminary cellular assays demonstrated that the PLGA-gold nanoparticles are cytocompatible, with both FibH and HeLa cells exhibiting a cellular viability of approximately 100%. ConclusionThus, these results underline the potential the PLGA-gold nanoparticles, particularly formulation A, for advanced applications in nanomedicine. In the future the encapsulation of drugs will be evaluated in order to characterise both the uptake and the cytotoxic capacity of this multifunctional nanomaterial. Additionally, the utilization of more complex in vitro models, such as tumor spheroids and animal models, will then be essential to determine the therapeutic potential of PLGA/gold nanoparticles.